2016
DOI: 10.5935/abc.20160041
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Insulin Resistance with Anthropometric Measures and Blood Pressure in Adolescents

Abstract: BackgroundBlood pressure is directly related to body mass index, and individuals with increased waist circumference have higher risk of developing hypertension, insulin resistance, and other metabolic changes, since adolescence.Objectiveto evaluate the correlation of blood pressure with insulin resistance, waist circumference and body mass index in adolescents.MethodsCross-section study on a representative sample of adolescent students. One group of adolescents with altered blood pressure detected by casual bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
2
11
1
5
Order By: Relevance
“…Mechanisms explaining the effect of obesity on male fertility include abnormal reproductive hormone levels, increased release of adipose-derived hormones and adipokines associated with obesity, and other physical problems including sleep apnea and increased scrotal temperatures [ 39 ]. In our study, the correlation between pairs of clinical features of the study population was positive between HOMA-IR and waist circumference, BMI, SBP, fasting glucose, and fasting insulin, in accordance with previous reports [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Mechanisms explaining the effect of obesity on male fertility include abnormal reproductive hormone levels, increased release of adipose-derived hormones and adipokines associated with obesity, and other physical problems including sleep apnea and increased scrotal temperatures [ 39 ]. In our study, the correlation between pairs of clinical features of the study population was positive between HOMA-IR and waist circumference, BMI, SBP, fasting glucose, and fasting insulin, in accordance with previous reports [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…(25) On the other hand, the correlation of HOMA-IR with the BMI percentile (r=0.198; p=0.037) found in this study is lower than that reported with anthropometric parameters in adolescents from Jalisco, Mexico (BMI: r=0.27; p<0.001), Brazil (BMI: r=0.366; p=0.031) and Chile (BMI: r=0.327; p<0.0001). (26)(27)(28) According to the body weight analysis, the overweight and obese group had higher insulin and HOMA-IR levels than the normal weight group (p=0.010 and p=0.015), trend that has been reported in adolescents from Peru and Venezuela. (29,30) For several years, IR has been described as a high impact factor for the alteration of the level of triglycerides and HDL cholesterol, lipids closely related to the development of metabolic syndrome in both adult and adolescent population.…”
Section: Discussionmentioning
confidence: 67%
“…The same cut-off value was used by authors in Košice (Slovakia) in a group of 224 high school students with an average age of 18 years and found only a 13.9% prevalence of IR [50]. The IR prevalence in a relatively small sample of Brazilian children (n=162) aged 12-18 years was slightly higher, 23.5% at the same cut-off point of 3.16, but at overweight/obesity prevalence of 45.7% [51]. However, if we used the lowest recommended cut-off values [47], the prevalence of IR would increase to 53.7% (males) and 68.3% (females).…”
Section: Discussionmentioning
confidence: 99%